HTML5 & CSS3 fundamentals LiveLessons (sneak peak video training) - Deitel, Paul J. (Prentice Hall, 2012)
"You start by learning the basics of HTML5, then cover more sophisticated techniques such as creating tables, creating forms for collecting user input and using new features in HTML5, including page-structure elements that enable you to give meaning to the parts of a page (e.g., headers, navigation areas, footers, sections, figures, figure captions and more). Then you move on to the canvas element, which provides a JavaScript application programming interface (API) with methods for drawing two-dimensional bitmapped graphics and animations, manipulating fonts and images, and inserting images and videos ... You learn CSS basics, then you go on to the key new features in CSS3, including text and box shadows, transitions, transformations, animations, multicolumn layouts and more. Finally, you learn about two new important HTML5 technologies: Web Workers and WebSockets."--Resource description page.